Formas de sociabilidade entre alunos de uma Escola de Ensino Técnico/Médio - Sara Villas (2009)
This work is inserted on the Sociology of Education field and is proposed to make an etnographic research on the sociability forms among students on a secondary/technician school on a federal instituition. The specificity on its double form of students selection by tests, in which students are divided into three socialeconomic cathegories, or by automatic admission for students who come from primary school on the same institution produces a relatively cultural and socialeconomical diversity among alumni, impacting the sociability forms on the group. The questions that oriented this researh were: what the sociability forms among students at this school? How, everyday, cultural practices and the relation with studies with the school interfere on the afinity groups formation? Which the schools role, today, as primary sociability space? With the empirical research I tried to produce sociological interpretations to the sociability phenomena on schools everyday, as well as turning intelligible the complexity in which this forms of relation are wrapped. The data we have collected during observation, on discussion groups and on questionnaire were analysed acording to Simbolic Interactionisms and Ethnomethodologys theoricalmethodological principles. For doing so, I based myself on the Hérans (1988), Santos (1994) and Simmels (2006) works, on the sociability theorical concepts, and on Abrantes (2003), Dayrell (1999, 2001, 2004, 2007), Lopes (1996) and Willis (1991), with their studies about the youth sociability on school. The research revealed that friendship relations and afinity groups have a significant interference on the youth identity construction; the way how school is constituted as a singular space for sociability fomentation; the stigma and stereotypes production generated by institutional status differences and by the forms of relation with study and school. It was possible, therefore, to elicit the both social and contextual nature of sociability forms.